The case of the sneaker sneak - Preller, James; Smith, Jamie, 1971- (New York : Scholastic, 2001)
After someone steals Bigs's football shoes before the game of girls against boys, it's up to Jigsaw and Mila to investigate and retrieve the stolen sneakers.
"A Little Apple paperback."
Smith, Jamie.
"RL2 006-009"--Page 4 of cover.
Accelerated Reader
Reading Counts
Lexile
Keywords: Football stories; Competition (Psychology) -- Juvenile fiction; Lost articles -- Juvenile fiction; Shoes -- Fiction; Football -- Fiction; Competition -- Fiction; Lost and found possessions -- Fiction; Mystery and detective stories; School fiction; Detective and mystery fiction; Detective and mystery fiction; Fiction; Juvenile works